Applied Linguistics: thematic pursuits or disciplinary moorings?: A conversation between Michael Halliday and Anne Burns. Issue 1 (24th August 2015) - Halliday, M.A.K.; Burns, Anne
Abstract : This is a condensed and edited version of the conversation which was recorded on 21 December, 2005 at Macquarie University, Sydney. This paper has been published as Halliday (2007).